State of harmful entomocomplex in winter wheat crops in Ukraine under the conditions of climate change - Borzykh, O.; Chaika, V.; Fedorenko, A.; Borusenko, V.; Neverovska, T.; Vlasenko, I.; Miniailo, N. (Quarantine and plant protection, 2022)
Goal. To establish the multi-year dynamics of the number of the main pests of winter wheat and the indicator of entomological diversity of agricultural landscapes in the conditions of climate change in Ukraine. Methods. Laboratory, statistical and analytical. The state of populations during 2005—2017 was studied using the example of an indicator group of species — the entomological complex of the main pests of winter wheat crops. As initial data, a long-term database of the number of populations of the entomocomplex in different natural and climatic zones, which is monitored by specialists of the phytosanitary safety department of the State Production and Consumer Service of Ukraine, was used for many years. Results. According to the analysed data on the state of indicator populations during 2009—2017, the indicators of the population size and weighted LPI were constantly decreasing. The correlation between the size of an insect’s population and the course of natural warming does not make it possible to unambiguously explain the state of populations by the effect of an increased amount of heat. Conclusions. 1. The analysis of the long-term state of populations of a harmful entomocomplex of winter wheat as an indicator group shows that pests react differently to warming depending on the biology of the species and allows us to come to a conclusion about the gradual decrease in the number of insects in agricultural landscapes under conditions of climate warming in Ukraine. This finding is in good agreement with the literature on global depletion of invertebrate populations. 2. Under the conditions when most species of the harmful entomocomplex of winter wheat in different natural and climatic zones of Ukraine show depression against the background of global warming, planned chemical treatments against pests should be carried out only after careful phytosanitary monitoring of agrocenoses in order to clarify the degree of threat to the crop, which will help reduce pesticide load on the natural environment.